Analisis Jenis-Jenis Bullying dan Dampaknya Terhadap Psikologi Peserta Didik MTs Negeri Ambon - Lating, Ainun Diana; Mahaly, Sawal; Ellis, Rusnawati; Jumail, Jumail; Lessy, Dara Umi (Indonesian Journal of Counseling and Development, 2024)
Bullying in school environments is a concerning social issue due to its serious impact on students’ mental health. This study aims to analyze the types of bullying experienced and their psychological effects on students at MTs Negeri Ambon. A descriptive quantitative approach was used, involving all 193 eighth-grade students as the sample through total sampling technique. The findings show that verbal bullying was the most common form experienced (35.75%), followed by social bullying (24.87%), cyberbullying (21.76%), and physical bullying (17.62%). The most dominant psychological impact reported was anxiety (34.72%), followed by low self-esteem (27.46%), mild depression (22.28%), and post-bullying trauma or stress (15.54%). These results highlight the urgency of preventive and comprehensive interventions, particularly targeting verbal and social bullying, in order to protect students’ psychological well-being